(untitled) (Journal of the College of Basic Education, 2025)
The aim of the current research is to know the effect of the Galen’s strategy on the achievement of mathematics among first-year middle school female students and the development of decision-making skills. The research sample consisted of (80) students from first- year middle school female students from Al-yaqitha middle School affiliated with the Baghdad Al-Karkh Education Directorate /2, The sample was randomly distributed into two experimental and control groups, with (40) female students for both groups. The experimental group studied according to the Galen’s strategy and the control group studied according to the usual method. The two groups were equalized in terms of intelligence, previous knowledge in mathematics, chronological age (calculated in months). The researchers prepared their research tools. The first tool was an achievement test in mathematics consisting of (40) multiple-choice items that included the six levels of Bloom’s cognitive domain. And they prepared a measure for developing decision-making skills consisting of (15) multiple-choice items. The test consisted of five sub-skills. The data was processed statistically with the following statistical methods: t-test for two independent samples, difficulty coefficient, discriminatory power, and reliability. The research results showed that there was a statistically significant difference at the level (0.05) between the average scores of the female students of the experimental and control groups in the achievement test in favor of the experimental group who studied according to the Galen’s strategy. Several recommendations were made, including: conducting a study similar to the current study for other stages and different academic subjects